The bank credit analysis handbook : a guide for analysts, bankers and investors - Golin, Jonathan L.; Delhaise, Philippe (Chichester : John Wiley, 2013)
The handbook of theory and practice in bank credit analysis and ratings, fully updated and revised The Bank Credit Analysis Handbook, Second Edition explains the role and methodologies of bank credit analysts, giving both investors and practitioners an insider's perspective on how rating agencies assign all-important credit ratings to banks.
Includes bibliographical references and index.
rua 23/06/15
Loans
Keywords: Banks and banking; Credit